AGGRESSIVEâ€ CLEAR CELL CHONDROSARCOMA OF THE HARD PALATE - Bhandarkar, Ajay M; Ramaswamy, Balakrishnan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Chondrosarcomas constitute 1 to 3% of all head and neck tumours. 2% of all chondrosarcomas are of the clear cellâ€ variety which follow a locally aggressive, relatively indolent course without predominant invasion of soft tissue. We present aÂ 45-year-old woman presented with a bleeding mass in the oral cavity with change of voice of one year duration with pain of one month duration and histopathological analysis revealed a clear cell chondrosarcoma.